Avaliação do tratamento dos resíduos sólidos em uma unidade escolar como instrumento para um plano de gestão - Farias Junior, Samuel Gomes de (Universidade Federal de São Carlos, 2022)
Since the humanity stop being errant and started to fix residency, the residue accumulation has been an issue. So much so, that after the industrialization this matter reached an alarming point, and nowadays it takes a main role in any discussion about a sustainable future. This final paper’s subject is the solid wast management of a school with 471 students and 55 employees, technical visits were made and also a survey for 48 employees to answer. The results show a lack of communication in the institution about that topic and the nonexistence of a organized system of solid waste management. At the end of this study the need for an environmental education campaign stood out and it has to be done for the whole school community. Even though a solid waste management is not mandatory in schools it is an important tool for an environmental education.
Evaluation of solid waste treatment in a school unit as an instrument for a management plan
Keywords: Gerenciamento de resíduos sólidos; Unidade escolar; Gestão ambiental; Solid waste management; School; Environmental management; ENGENHARIAS